1996
DOI: 10.1007/bf00301252
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord compression resulting from Burkitt's lymphoma in children

Abstract: We report seven cases of spinal cord compression resulting from Burkitt lymphoma in boys aged 15 years and below. This became manifest clinically as acute or rapidly progressive spinal cord compression. All the patients showed total paraplegia with a sensory loss at thoracic level and sphincter disturbances. Four patients were operated on, the operation permitting exeresis of an epidural tumor. In three cases surgery was followed by chemotherapy. One patient was treated exclusively with chemotherapy. Owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
3
10
0
2
Order By: Relevance
“…Boggan reported that surgical treatment should be limited to the cases based on the severity and chronicity of preoperative damage (19). In contrast, the improvement of pituitary abscess only with medication consisting of administration of CTX and metronidazol for 1 month and netilmicin for 15 days was also reported (20) …”
Section: Causes Of Pituitary Abscess Have Been Suggested As Follows: mentioning
confidence: 97%
“…Boggan reported that surgical treatment should be limited to the cases based on the severity and chronicity of preoperative damage (19). In contrast, the improvement of pituitary abscess only with medication consisting of administration of CTX and metronidazol for 1 month and netilmicin for 15 days was also reported (20) …”
Section: Causes Of Pituitary Abscess Have Been Suggested As Follows: mentioning
confidence: 97%
“…Furthermore, surgical intervention may delay the administration of systemic chemotherapy, the definitive treatment for BL. Surgery may be warranted for various complications that can be related to BL, such as intestinal perforation, bleeding, or obstruction, refractory gastric outlet obstruction, or spinal cord instability [62,63].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Laminectomy should only be considered when rapid deterioration under chemotherapy is observed. 14,15 Evidence to support this approach is also derived from studies of medullar compression due to neuroblastoma and tumoral metastases. 16,17 The reduced immunity in HIV-infected patients with lymphoma makes them more susceptible to the toxic effects of cytostatics, hence a higher risk exists of severe, lifethreatening infections during chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Polychemotherapy combining cyclophosphamide, methotrexate, vincristine, and cytarabine has been shown to be highly effective in most cases. 14 Serious complications such as hematoma, infection, cerebrospinal fluid fistula, nerve root damage, arachnoiditis, and spinal instability have been described after emergency laminectomies. 9 In view of evidence of the high sensitivity of the tumor to chemotherapy, a spinal compression due to Burkitt lymphoma is seen primarily as a nonsurgical disease.…”
Section: Discussionmentioning
confidence: 99%